2012
DOI: 10.1038/nrurol.2012.177
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for intrinsic sphincter deficiency

Abstract: Type III stress urinary incontinence (SUI) is generally defined as a condition that involves intrinsic sphincter deficiency (ISD). Although the clinical parameters for ISD are loosely defined as a Valsalva leak-point pressure <60 cmH(2)O or a maximal urethral closure pressure <20 cmH(2)O, consensus is lacking. As a result, studies evaluating the success of any treatment for ISD are difficult to interpret. Regardless, several studies over the past 20 years have evaluated a number of surgical and nonsurgical tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 83 publications
0
9
0
1
Order By: Relevance
“…Partial defects include laxity, fluttering or focal attenuation of ligaments. Complete disruption shows a discontinuity of ligamentous fibers [6,12] ; mostly affected and reproducibly visualized on imaging is PEL and pubourethral ligaments [10] . Findings are frequently accompanied by the abnormal vaginal configuration (loss of normal Hshape vaginal contour, or dropping vaginal fornix), best seen on axial images, and widening of the paravaginal attachments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial defects include laxity, fluttering or focal attenuation of ligaments. Complete disruption shows a discontinuity of ligamentous fibers [6,12] ; mostly affected and reproducibly visualized on imaging is PEL and pubourethral ligaments [10] . Findings are frequently accompanied by the abnormal vaginal configuration (loss of normal Hshape vaginal contour, or dropping vaginal fornix), best seen on axial images, and widening of the paravaginal attachments.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Sand et al [5] studied women who failed retropubic suspension and found a higher failure rate in those with ISD. It has been shown that SUI caused by ISD is the most challenging to treat; with failure rates as high as 54% [6] . These failures were attributed to the correction of UH without concomitant increase of urethral closure pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who were diagnosed with SUI with urethral hypermobility and in whom conservative treatments had failed were included. SUI patients with intrinsic sphincter deficiency, defined as a Valsalva leak-point pressure of <60 cm H 2 O, were excluded [16]. Other exclusion criteria were mixed urinary incontinence (MUI), pelvic organ prolapse (POP) greater than stage I (POP-Q system classification), and a past history of hysterectomy and pelvic reconstruction surgeries.…”
Section: Methodsmentioning
confidence: 99%
“…A urethral closure pressure less than 20 cm of water or a leak point pressure less than 60 cm of water is commonly termed intrinsic sphincteric deficiency. [33][34][35][36] The presence of intrinsic sphincteric deficiency has meaning when treatment options are discussed. The size of the catheter can influence the result, because larger catheters will obstruct the urethra more than smaller ones.…”
Section: Objective Testingmentioning
confidence: 99%